Dilemma of Full Day School in Islamic Education in Indonesia - Ahmad Muzammil Kholily (Didaktika Religia, 2017)
This article aims to explore the implementation of full day school in Islamic education in Indonesia. The position of Islamic education in the national education system is a kind of religious character education, so Islamic education in sisdiknas should be able to organize formal education institutions, non formal and informal, from the basic level to college, managed by the government or/and private institution. In this case, the government also creates an organizational structure in running Islamic education programs in Indonesia. Regulation of Minister of Education No. 23 of 2017 about full day school certainly contribute to the conflict of Islamic education in Indonesia because full day school is not accepted by the majority of scholars or the santri because it is realized that the regulation is problematic for Islamic education, especially madrasah diniyah , for students and teachers. Full day school (FDS) program is actually not new in education, such as boarding school education institutions. The education program at boarding school is not only Full Day School (FDS) but full years school or running for 24 hours, where the process of education is not only in formal lesson time.